Geographic Indonesia April 2020 Issue - Titah Madriyanthi Utama, Luh Gde; Udayana, I Nyoman (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2021)
This research aims to study news translation in magazines, specifically about textual manipulation which occurred in the National Geographic Indonesia April 2020 issue. The analysis applied the theory of translation strategies by Chesterman (2016) but only referred to the syntactic strategy. This study also applied a qualitative method and the analysis is presented descriptively. The analysis revealed the textual changes that occurred in the articles in the National Geographic Indonesia Magazine April 2020 issue. Textual manipulations are the results of the application of translation strategies which are observable through the comparison of both the translation product itself and the original text. Therefore, they can be linked with Chesterman’s syntactic strategies which are found in the data. Based on the data analysis, the following strategies were found, they are literal translation, loan or calque, transposition, unit shift, phrase structure change, clause structure change, sentence structure change, cohesion change, and level shift.